Insatisfação com o trabalho e ocorrência de transtornos mentais comuns entre trabalhadores de Saúde - Sousa, Camila Carvalho de (2017)
Job dissatisfaction is a complex phenomenon and depends on internal and external influences to the work environment. It is closely related to the physical and mental health of the worker. However, the association between job dissatisfaction and mental illness has been little explored in the literature. The present study aimed to analyze the job dissatisfaction, referred to by the health care workers of basic care and medium complexity, considering their determinants and effects on mental health (occurrence of common mental disorders - CMD), with specific objectives: describe job dissatisfaction according to sociodemographic aspects and general characteristics of work; to estimate levels of dissatisfaction; to estimate the frequency of CMD; to investigate the association between occupational stress and job dissatisfaction; investigating the association between job dissatisfaction and CMD; considering gender differentials in the estimated associations. A cross-sectional study was conducted in five counties, in Bahia, with 3084 health workers from the medium complexity and primary care services between 2011 and 2012. The results of this dissertation are presented in the format of three scientific articles. In the first article, the job dissatisfaction was evaluated considering the sociodemographic characteristics and general information about the work, the analysis was stratified by gender. It was verified that aspects related to the sexual division of work were positively associated with the levels of job dissatisfaction. In the second article, was evaluated the association of psychosocial aspects of work and job dissatisfaction, based on the combination of occupational stress models (Effort-Reward Imbalance - ERI (mensured by Effort-Reward Imbalance Scale) and Demand-Control Model –DCM (measured by Job Content Questionnaire - JCQ). The combination of the models proved to be advantageous in investigating the outcome. The third article, analyzed the relationship between job dissatisfaction, referred to by health care workers of basic care and medium complexity, and the occurrence of CMD, using modeling of structural equations. The job dissatisfaction had a direct and positive effect on CMD. The findings reinforce the impact of psychosocial aspects on job dissatisfaction and the impact of job dissatisfaction onmental health with women being the group in which these relationships were more expressive, indicating greater exposure.